The association between apelin-12 levels and paroxysmal supraventricular tachycardia - Gurger, Mehtap; Celik, Ahmet; Balin, Mehmet; Gul, Evrim; Kobat, Mehmet A.; Bursali, Kazim B.; Aydin, Suleyman (Lippincott Williams & Wilkins, 2014)
Aims Our aim was to investigate the apelin-12 levels in patients with atrioventricular tachyarrhythmias and compare with those in patients with lone atrial fibrillation. Methods Forty four patients with supraventricular tachycardia as atrial fibrillation, 44 patients with paroxysmal supraventricular tachycardia (P-SVT) as atrioventricular tachyarrhythmias, including atrioventricular nodal reentrant tachycardia or atrioventricular reentrant tachycardia, and 30 age-and sex-matched healthy individuals were included in the study. Results The apelin-12 levels were significantly lower in both atrial fibrillation and P-SVT groups than control group. In post-hoc analysis, there was no significant difference in apelin-12 levels between atrial fibrillation and P-SVT groups (P=0.9). Patients in atrial fibrillation group and patients in P-SVT group had significantly lower apelin-12 levels than control group, separately (P<0.001 and P<0.001, respectively). The sensitivity and specificity values of the apelin-12 levels for predicting SVT, including both atrial fibrillation and atrioventricular reentrant tachycardia or atrioventricular nodal reentrant tachycardia were 64.77 and 90%, respectively (cut-off value was 0.87). The area under the receiver operator characteristic curve was 0.834 for the apelin-12 levels (P=0.0001). Conclusion Apelin-12 levels are lower in patients with atrial fibrillation and P-SVT than control groups. Lower apelin levels in patients with atrial fibrillation and P-SVT would be expected to result in a decrease in the conduction velocity.
Keywords: apelin 12; atrioventricular nodal reentrant tachycardia; atrioventricular reentrant tachycardia; paroxysmal supraventricular tachycardia